Developing a competency framework for academic physicians. (4th March 2017) - Daouk-Öyry, Lina; Zaatari, Ghazi; Sahakian, Tina; Rahal Alameh, Boushra; Mansour, Nabil
Abstract: Background: There is a mismatch between the requirements of the multifaceted role of academic physicians and their education. Medical institutions use faculty development initiatives to support their junior academic physicians, however, these rarely revolve around academic physician competencies. The aim of this study was to identify these academic physician competencies and develop a competency framework customized to an organizational context. Methods: The authors conducted semi-structured interviews and Critical Incident Technique with 25 academic physicians at a teaching medical center in the Middle East region inquiring about the behaviors of academic physicians in teaching, clinical, research, and administrative roles. Results: Using content analysis, the authors identified 16 competencies: five "Supporting Competencies", common to all four roles of academic physicians, and 11 "Function-Specific Competencies", specific to the role being fulfilled. The developed framework shared similarities with frameworks reported in the literature but also had some distinctions. Conclusions: The framework developed represents a step towards closing the gap between the skills medical students are taught and the skills required of academic physicians. The model was customized to the context of the current organization and included a future orientation and addressed the literature calling for increasing focus on the administrative skills of academic physicians.